Are cytokines useful biomarkers to determine disease severity in neonates with congenital diaphragmatic hernia? - Schaible, Thomas; Reineke, Janine Margaux; Schaffelder, Regine (American journal of perinatology, 2017)
Background: This study investigates plasma cytokine levels in neonates with the more common left-sided congenital diaphragmatic hernia (CDH) and correlates them with severity of disease indicated by position of the liver. An intrathoracic part of liver is associated with higher need for extracorporeal membrane oxygenation (ECMO) and higher risk for chronic lung disease (CLD). Methods: A total of 28 newborns with CDH were subdivided by their liver position in partially intrathoracic (n = 16) and only abdominal (n = 12) position. Only liver-up patients went on ECMO (n = 9) and developed severe/moderate CLD (n = 5). Controls consisted of 19 healthy matched-term neonates. Laboratory samples were extracted from umbilical cord blood and during the neonatal period. Results: In umbilical cord blood, CDH patients showed decreased IL-8 values while MIP-1a (macrophage inflammatory protein-1) values were increased. Concerning the severity of CDH, we measured significantly higher levels of TGFb2 in CDH patients with liver-up than in liver-down cases and controls (p < 0.006). During the neonatal period, the concentration of IL-10 and vascular endothelial growth factor (VEGF) showed significant deviations in the liver-up group with need for ECMO (p < 0.009). Conclusion: In neonates with CDH, plasma cytokine levels are already altered in utero. TGFb2 may work as an early predictor for severity of disease. VEGF and IL-10 could serve as potential biomarkers predicting the course of disease in CDH.
Published online: December 7, 2016
Gesehen am 10.04.2018